2022
DOI: 10.2215/cjn.16831221
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Involved in Chronic Kidney Disease of Unclear Etiology

Abstract: Background and objectivesThe etiology of chronic kidney disease of unclear etiology, also known as Mesoamerican nephropathy, remains unclear. We investigated potential etiologies for Mesoamerican nephropathy in an immigrant dialysis population.Design, setting, participants, & measurementsMigrants with Mesoamerican nephropathy kidney failure (n=52) were identified by exclusion of known causes of kidney disease and compared using a cross-sectional survey with demographically similar patients with kidney fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…Evidence for nephrotoxin-induced injury is present in Central America, where 1 year of agrochemical exposure was significantly associated with CKDu, with OR 4.86, P less than 0.002 and OR 12.25, P less than 0.02 for agrochemical and paraquat exposure, respectively [28 ▪▪ ]. Longer and more frequent exposures resulted in higher risk with or without PPE use.…”
Section: Pathogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence for nephrotoxin-induced injury is present in Central America, where 1 year of agrochemical exposure was significantly associated with CKDu, with OR 4.86, P less than 0.002 and OR 12.25, P less than 0.02 for agrochemical and paraquat exposure, respectively [28 ▪▪ ]. Longer and more frequent exposures resulted in higher risk with or without PPE use.…”
Section: Pathogenesismentioning
confidence: 98%
“…Longer and more frequent exposures resulted in higher risk with or without PPE use. Similarly, Central American migrants in the United States showed an association between chronic intermittent agrochemical exposure, particularly paraquat, and kidney failure [28 ▪▪ ]. In Mexico, agrochemicals have been potentially associated with impaired kidney function and proteinuria [29].…”
Section: Pathogenesismentioning
confidence: 99%
“…In this issue of CJASN , Holliday et al . (4) attempt to investigate a specific agrochemical, paraquat, as a potential etiologic agent for CKDu using a clinic-to-benchside approach. Their approach is reminiscent of the approach that ultimately identified Balkan endemic nephropathy, the closest historical corollary of CKDu, as resulting from aristolochic acid exposure.…”
mentioning
confidence: 99%
“…Similarly, although in reverse order, Holliday et al (4) first identified 52 patients matching the case definition of Mesoamerican nephropathy receiving dialysis care at the Harris Health System in Houston, and two sets of Latin American immigrant participants serving as controls. The first control set of 63 patients was also receiving dialysis and had a specific cause of kidney disease identified; a second set of 16 participants were matched for age and country of origin but did not have kidney disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation